Opportunities for Using Complexity-Aware Approaches to Theory of Change - Goodier, Sarah; Apgar, Marina (IDS, 2018)
The purpose of this briefing note is to review opportunities for using complexity aware approaches to Theory of Change (ToC) to inform the SDC approach. It provides an overview of complexity-aware approaches and then focuses on demonstrating how complexity thinking can support programming by building on the frameworks currently being used in the project/programme cycle management (PCM) processes. It is aimed at SDC staff, in particular Programme Officers and staff of partner organisations involved in the management of SDC interventions.

Bringing Participation into Complexity-Aware MEL: What is the evidence? - Apgar, Marina; Higdon, Grace Lyn (2018)

State of the Art on Use of Theory of Change in the Development Sector - Goodier, Sarah; Apgar, Marina; Clark, Louise (IDS, 2018)
The purpose of this briefing note is to add to SDC’s understanding of Theory of Change (ToC), drawing on the literature and practice to sketch out the current state of the art approach. This involves expanding on ToC beyond SDC’s current practice of using Impact Hypotheses (IH) to bridge it to operational practice and use ToC more explicitly in the project/programme cycle management (PCM) processes. Sharing the state of the art on use of ToC in the development sector, this briefing note outlines what a ToC is, what it is used for and why it is needed in the development sector. It discusses ToC as both a process and a product, providing step by step guidance on how to facilitate a ToC process. The differences between a ToC and a logframe are highlighted. Some key criteria for recognising when you have a ‘good’ ToC are also included. This brief is aimed at SDC staff, in particular Programme Officers, and staff of partner organisations involved in the management of SDC interventions.